An improvised apparatus for high school physics to demonstrate photoelectric effect - Oalin, Leticia A. 1948-
The aim of this study was to improvise an apparatus and develop laboratory activities which can be used to investigate photoelectric effect. This paper is done in an effort to help ease the problem of the lack of apparatus and to contribute toward an increasing awareness amongst students about the role of technology in society. Photoelectric effect is a phenomenon which is the basis of many technological devices and for which no laboratory exercise appropriate for the level of fourth year high school students has been developed.